67 Design and rationale for an implementation trial to improve care for low back pain in emergency departments. (20th August 2018) - Machado, Gustavo; Richards, Bethan; Needs, Chris; Buchbinder, Rachelle; Harris, Ian; Howard, Kirsten; McCaffery, Kirsten; Billott, Laurent; Oliver, Matthew; Rogan, Eileen; Facer, Rochelle; Cowell, David Lord; et al.
Abstract : Objectives: When low back pain is managed in the emergency department overdiagnosis and overtreatment are common. Key problems are overuse of imaging, opioid medicines and hospital admission. The overall aim of the Sydney Health Partners Emergency Department (SHaPED) trial is to implement and evaluate an evidence-based model of care for acute low back pain. The outcomes of the trial reflect the key messages in the model: (1) patients with non-specific low back pain do not require imaging; (2) where medicines are used, simple analgesics should be the first option; (3) patients with non-specific low back pain should be managed as outpatients. Method: A stepped-wedge cluster randomised controlled trial will be conducted to implement and evaluate the model of care for acute low back pain at four emergency departments in New South Wales, Australia. Clinician participants will be emergency physicians, nurses and physiotherapists. Codes from the Systematised Nomenclature of Medicine—Clinical Terms—Australian version will be used to identify low back pain presentations. We anticipate 2000 patient participants. The intervention, targeting emergency clinicians, will comprise educational materials and seminars and an audit and feedback approach. Health service delivery outcomes are routinely collected measures of imaging (primary outcome), opioid use and inpatient admission A random subsample of 200 patient participants from each trial period will be included to measure patient outcomes (pain intensity, physical function, quality of life and experience with emergency service). An economic evaluation will be undertaken from the health system perspective. Results: The SHaPED trial received ethical approval from the RPAH HREC (reference: X17–0043). The trial is registered with the Australia New Zealand Clinical Trials Registry: ACTRN 12617001160325.The conference presentation will discuss the design and rationale for the trial. Conclusions: We hypothesised that active implementation of an evidence-based model of care for low back pain will improve emergency care by reducing inappropriate overuse of tests and treatments (i.e. imaging, opioids, admission to hospital) and improving patient outcomes.